Glycated Albumin for Glycemic Control in T2DM Population: A Multi-Dimensional Evaluation - Ferrario L; Schettini F; Avogaro A; Bellia C; Bertuzzi F; Bonetti G; Ceriello A; Ciaccio M; Corsi Romanelli M; Dozio E; Falqui L; Girelli A; et al. (Dove Medical Press, 2021)
Lucrezia Ferrario,1 Fabrizio Schettini,1 Angelo Avogaro,2 Chiara Bellia,3 Federico Bertuzzi,4 Graziella Bonetti,5 Antonio Ceriello,6 Marcello Ciaccio,3,7 Massimiliano Corsi Romanelli,8,9 Elena Dozio,9 Luca Falqui,10 Angela Girelli,11 Antonio Nicolucci,12 Gianluca Perseghin,13,14 Mario Plebani,15 Umberto Valentini,11 Martina Zaninotto,15 Silvana Castaldi,9,16 Emanuela Foglia1 1Centre for Health Economics, Social and Health Care Management, Università Carlo Cattaneo - LIUC, Castellanza, Italy; 2Department of Medicine, University-Hospital of Padova, Padova, Italy; 3Section of Clinical Biochemistry and Clinical Molecular Medicine, Department of Biopathology and Medical Biotechnologies, University of Palermo, Palermo, Italy; 4Diabetology Unit, Grande Ospedale Metropolitano Niguarda Hospital, Milan, Italy; 5Department of Medicine Services, Valcamonica Hospital, Esine, Italy; 6Department of Cardiovascular and Metabolic Diseases, Multimedica Research Institute, Milan, Italy; 7Department of Laboratory Medicine, University-Hospital of Palermo, Palermo, Italy; 8Service of Laboratory Medicine 1-Clinical Pathology, Policlinico San Donato, Milan, Italy; 9Department of Biomedical Sciences for Health, Università degli Studi di Milano, Milan, Italy; 10Department of Medicine, Diabetes and Endocrinology, Multimedica Research Institute, Milan, Italy; 11Diabetes Care Unit, Spedali Civili Hospital, Brescia, Italy; 12Center for Outcomes Research and Clinical Epidemiology, Pescara, Italy; 13Department of Medicine and Surgery, Università degli Studi di Milano Bicocca, Milan, Italy; 14Department of Medicine and Rehabilitation, Unit of Metabolic Medicine, Policlinico di Monza, Monza, Italy; 15Department of Laboratory Medicine, University-Hospital of Padova, Padova, Italy; 16Fondazione Ca’ Granda Ospedale Maggiore Policlinico Research Institute of Milano, Milano, ItalyCorrespondence: Lucrezia FerrarioCentre for Health Economics, Social and Health Care Management, Università Carlo Cattaneo – LIUC, Corso Matteotti 22, Castellanza, 21053, VA, ItalyTel +39 033 1572504Fax +39 033 1572513Email lferrario@liuc.itPurpose: To investigate the glycated albumin (GA) introduction implications, as an add-on strategy to traditional glycemic control (Hb1Ac and fasting plasma glucose – FPG) instruments, considering insulin-naïve individuals with type 2 diabetes mellitus (T2DM), treated with oral therapies.Methods: A Health Technology Assessment was conducted in Italy, as a multi-dimensional approach useful to validate any innovative technology. The HTA dimensions, derived from the EUnetHTA Core Model, were deployed by means of literature evidence, health economics tools and qualitative questionnaires, filled-in by 15 professionals.Results: Literature stated that the GA introduction could lead to a higher number of individuals achieving therapeutic success after 3 months of therapy (97.0% vs 71.6% without GA). From an economic point of view, considering a projection of 1,955,447 T2DM insulin-naïve individuals, potentially treated with oral therapy, GA introduction would imply fewer individuals requiring a therapy switch (− 89.44%), with a 1.06% in costs reduction, on annual basis, thus being also the preferable solution from a cost-effectiveness perspective (cost-effectiveness value: 237.74 vs 325.53). According to experts opinions, lower perceptions on GA emerged with regard to equity aspects (0.13 vs 0.72, p-value> 0.05), whereas it would improve both individuals (2.17 vs 1.33, p-value=0.000) and caregivers quality of life (1.50 vs 0.83, p-value=0.000). Even if in the short term, GA required additional investments in training courses (− 0.80 vs 0.10, p-value = 0.036), in the long run, GA could become the preferable technology (0.30 vs 0.01, p-value=0.018) from an organisational perspective.Conclusion: Adding GA to traditional glycaemic control instruments could improve the clinical pathway of individuals with T2DM, leading to economic and organisational advantages for both hospitals and National Healthcare Systems.Keywords: glycated albumin, type 2 diabetes mellitus, T2DM, Health Technology Assessment, economic evaluation, multidimensional approach